Investigation and analysis of nurses' occupational well-being in a Traditional Chinese Medicine Green Nursing Clinic (中医绿色护理门诊护士职业幸福感的调查分析) - LIU Shanshan (刘姗姗); LI Suna (李苏娜); CHEN Hong (陈宏) (Association of Integrative Nursing, 2022)
Objective To investigate the status of occupational well-being of nurses in the Green Nursing Outpatient Department of a certain Traditional Chinese Medicine (TCM) hospital in Beijing. Methods A questionnaire survey was conducted on 59 nurses attending the TCM Green Nursing Clinic using the Medical Staff Occupational Well-Being Scale, and the data were analyzed. Results The total score of occupational well-being of nurses was (101. 17±15. 48), with five dimensional entries of social support (22. 19±3. 03), value/competence embodiment (26. 41±3. 63), work environment (14. 81±3. 02), economic income (10. 05±2. 84), physical and mental health (27. 71±2. 96), and the mean score of total entries (4. 22±0. 65) points, which was at a high level. Conclusion The nurses working in TCM Green nursing clinic were physically and mentally healthy, had a high degree of team working, and had a sense of achievement in work. They believed that lower sense of well-being was associated with the working environment and economic income. The high degree of occupational well-being of nurses is potentially effective to reduce nurse job burnout and increase the investment in outpatient work. It is suggested that TCM hospital managers should provide nurses with a platform to cultivate TCM nursing professional teams in outpatient clinics to solve practical problems and improve nurses' occupational well-being. (目的 调查北京市某三甲中医院中医绿色护理门诊护士职业幸福感现状。方法 采用医务人员职业幸福感量表对59名中医绿色护理门诊出诊护士进行问卷调查, 并对数据进行分析。结果 中医绿色护理门诊护士职业幸福感总分为(101. 17±15. 48)分, 五个维度条目中社会支持(22. 19±3. 03)分、价值/能力体现(26. 41±3. 63)分、工作环境(14. 81±3. 02)分、经济收入(10. 05±2. 84)分、身心健康(27. 71±2. 96)分, 总条目均分(4. 22±0. 65)分, 处于高等水平。结论 被调查医院中医绿色护理门诊护士身心健康发展, 团队磨合度高, 工作较有成就感, 但认为工作环境与经济收入方面较其他三者低。医护士的职业幸福感等级高可以减缓职业倦怠, 增加对门诊工作的投入度。建议各中医院给予护士平台, 培养门诊中医护理专业团队, 解决实际问题, 提高护士职业幸福感。)